Translanguaging and Educational Equity: A Narrative Review of Global Practices - Kuswidyasari , Ratih; Kasau, M Nurzin R (Lingua : Journal of Linguistics and Language, 2025)
This narrative review examines the role of translanguaging as a pedagogical framework in bilingual and multilingual education. Drawing on studies published in the last decade, the review synthesizes evidence on how translanguaging enhances comprehension, fosters identity affirmation, and promotes inclusive learning environments. Findings indicate that translanguaging improves academic performance by supporting conceptual understanding and learner engagement, while also validating students’ cultural and linguistic identities. Despite these benefits, systemic barriers such as monolingual ideologies, restrictive policies, and limited teacher preparation remain significant challenges. This review contributes by highlighting both the transformative potential and contextual limitations of translanguaging, and by identifying directions for future research on its long-term and cross-regional impacts.